Lithium supplement material and preparation method thereof, secondary battery and electric equipment

A lithium supplementation material with an iron-based core and layered lithium metal oxide shell addresses gas generation issues in secondary batteries, enhancing safety and cycle life by inhibiting ion oxidation and reducing side reactions.

CN119208606APending Publication Date: 2024-12-27SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411303843.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing lithium secondary batteries suffer from rapid gas generation during high-temperature storage, which poses safety hazards and reduces cycle life due to the formation of a solid electrolyte interface (SEI) layer and decomposition of active ions, leading to poor electrochemical stability and thermal stability.

Method used

A lithium supplementation material comprising a core of iron-based lithium-rich material with a non-metal element of higher electronegativity and a shell of layered lithium metal oxide is developed, which inhibits the oxidation of iron and oxygen ions, reducing side reactions and gas production.

Benefits of technology

The material improves the high-temperature storage performance and safety of secondary batteries by reducing gas generation and enhancing cycle life through the use of a specific layered lithium metal oxide shell and non-metallic elements like fluorine, chlorine, or bromine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048649090000131
    Figure BDA0005048649090000131
  • Figure BDA0005048649090000141
    Figure BDA0005048649090000141
Patent Text Reader

Abstract

The invention discloses a lithium supplement material and a preparation method thereof, a secondary battery and electric equipment. The lithium supplementing material comprises an inner core and a shell, the inner core comprises an iron-based lithium-rich material containing a non-metallic element with the electronegativity larger than that of an oxygen element, and the shell comprises a specific layered lithium metal oxide. The iron-based lithium-rich material is doped with specific non-metallic elements, and the specific layered lithium metal oxide is adopted as a shell component, so that the high-temperature storage performance of the secondary battery is improved, and the safety of the secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium supplementation, in particular to a lithium supplementation material, a preparation method thereof, a secondary battery and an electrical device. Background Art

[0002] Lithium secondary batteries have the advantages of high voltage, high energy density, and being unrestricted by terrain, etc., and have great application prospects in the field of large-scale energy storage. However, the cycle life of existing lithium secondary batteries is still relatively low. Therefore, the lithium supplementation technology has been developed to improve the cycle life of lithium secondary batteries. Lithium secondary batteries lose a part of lithium ions due to the formation of the SEI layer on the negative electrode during the first formation, which not only reduces the available capacity of the battery but also shortens the cycle life of the battery. Lithium-rich lithium supplementation agent materials can supplement the loss of lithium ions during the first and subsequent cycles of lithium secondary batteries due to their high irreversible capacity in the range of 3.0 - 4.5V, playing a role in extending the cycle life. The theoretical capacity of lithium-rich lithium supplementation agent materials is much higher than that of cathode materials such as lithium iron phosphate. Only a small amount of the lithium supplementation agent needs to be blended with the cathode powder particles to supplement the lithium ions lost during the first cycle of the battery, improving the available capacity and cycle times of the battery. However, when current lithium supplementation agents such as lithium-rich iron oxide (Li5FeO4) are used for cathode lithium supplementation, gas generation is rapid and the gas generation amount is large, bringing great potential safety hazards to the battery. Summary of the Invention

[0003] The purpose of the present application is to provide a lithium supplementation material, a preparation method thereof, a secondary battery and an electrical device to improve the problem of serious gas generation during high-temperature storage of existing lithium-supplemented secondary batteries.

[0004] To achieve the above purpose, in the first aspect of the present application, a lithium supplementation material is provided. The lithium supplementation material includes a core and a shell. The core includes an iron-based lithium-rich material, and the iron-based lithium-rich material contains a non-metal element with an electronegativity greater than that of oxygen element.

[0005] The shell includes a layered lithium metal oxide with the chemical formula Li a MO 2+q where 0.95 ≤ a ≤ 1.05, -0.05 < q < 0.05, and M includes at least one of Ru, Ga, In, Nb, and Mo.

[0006] As an embodiment of the present application, the non-metal element includes at least one of fluorine element, chlorine element, and bromine element.

[0007] As an embodiment of the present application, the iron-based lithium-rich material includes a chemical formula of Li x Fe y N z O 4-za compound, where 4.5 < x ≤ 5.0, 0.9 < y ≤ 1.0, 0 < z < 0.1, x + 3y = 8 - z, and N contains at least one of F, Cl, and Br.

[0008] As an embodiment of the present application, the average thickness of the outer shell is 2 - 25 nm.

[0009] As an embodiment of the present application, the mass of the outer shell accounts for 0.2% - 3.0% of the total mass of the lithium supplement material.

[0010] As an embodiment of the present application, the particle strength of the lithium supplement material is greater than or equal to 80 MPa.

[0011] In the second aspect of the present application, a method for preparing a lithium supplement material is provided, including the following steps:

[0012] S1. Mix the lithium source and the iron source evenly and then perform the first sintering in an oxygen atmosphere to obtain a primary sintered product, where the temperature of the first sintering is 450 - 600 °C and the time of the first sintering is 5 - 15 h;

[0013] S2. Mix the N source and the primary sintered product evenly and then perform the second sintering in an oxygen atmosphere to obtain a core material, where the temperature of the second sintering is 600 - 900 °C and the time of the second sintering is 24 - 72 h, and the N source contains at least one of LiF, LiCl, and LiBr;

[0014] S3. Mix the lithium source, the M source, and the core material evenly and then perform the third sintering in an oxygen atmosphere to obtain a lithium supplement material, where the temperature of the third sintering is 700 - 1000 °C and the time of the third sintering is 6 - 12 h.

[0015] As an embodiment of the present application, the lithium source includes at least one of LiOH, Li2O2, Li2O, and Li2CO3.

[0016] As an embodiment of the present application, the iron source includes at least one of FeOOH, FeO, and Fe2O3.

[0017] As an embodiment of the present application, the M source includes at least one of ruthenium dioxide, indium oxide, indium nitrate, gallium oxide, gallium nitrate, molybdenum oxide, and niobium oxide.

[0018] In the third aspect of the present application, a secondary battery is provided. The secondary battery includes a positive electrode plate, and the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode active material layer includes the lithium supplement material described in the first aspect of the present application or the lithium supplement material prepared by the preparation method described in the second aspect of the present application.

[0019] In a fourth aspect of the present application, an electrical device is provided, wherein the electrical device comprises the secondary battery described in the third aspect of the present application.

[0020] Compared with the prior art, the beneficial effects of this application are:

[0021] The present application provides a lithium supplement material, the lithium supplement material comprising a core and an outer shell, the core comprising an iron-based lithium-rich material containing a non-metallic element with an electronegativity greater than that of an oxygen element, and the outer shell comprising a specific layered lithium metal oxide. The present application improves the high-temperature storage performance of a secondary battery and enhances the safety of the secondary battery by doping a specific non-metallic element in the iron-based lithium-rich material and using a specific layered lithium metal oxide as an outer shell component. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0023] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0024] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0025] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0026] The first aspect of the present application provides a lithium supplement material, the lithium supplement material comprising a core and an outer shell, the core comprising an iron-based lithium-rich material, the iron-based lithium-rich material containing a non-metallic element with an electronegativity greater than that of an oxygen element;

[0027] The shell comprises a chemical formula of Li a MO 2+qLayered lithium metal oxide, where 0.95 ≤ a ≤ 1.05, -0.05 < q < 0.05, and M contains at least one of Ru, Ga, In, Nb, and Mo.

[0028] The inventors of the present application have found through research that in the formation process of existing lithium - supplemented iron - based lithium - rich materials, active iron ions and active oxygen ions are decomposed. These active ions have strong oxidizing properties and can oxidize electrolyte molecules, which will damage the composition and structure of the SEI film, and then cause instability of the negative - electrode SEI film. Especially at high SOC and high temperatures, the decomposition products react violently with carbonate molecules in the electrolyte, resulting in poor electrochemical stability and thermal stability at the interface of the negative - electrode active material, and a rapid increase in the amount of gases such as carbon monoxide and carbon dioxide generated. Non - metallic elements with electronegativity greater than that of oxygen in the iron - based lithium - rich materials can reduce the reactivity of iron and oxygen ions, thereby inhibiting the oxidation of iron and oxygen ions. At the same time, since a layered lithium metal oxide with a specific chemical formula is used as the coating material, the direct contact between active iron and oxygen ions and the acidic electrolyte can be reduced, and the side reactions between active iron and oxygen ions and the acidic electrolyte can be reduced, thereby reducing the volume expansion rate of the secondary battery during high - temperature storage and improving the safety of the secondary battery.

[0029] In some embodiments, the non - metallic element contains at least one of fluorine, chlorine, and bromine. Non - metallic elements such as fluorine, chlorine, and bromine have strong electronegativity, which can further reduce the reactivity of iron and oxygen ions, inhibit the oxidation of iron and oxygen ions, and improve the high - temperature storage performance of the secondary battery.

[0030] In some embodiments, the iron - based lithium - rich material contains a compound with the chemical formula Li x Fe y N z O 4-z where 4.5 < x ≤ 5.0, 0.9 < y ≤ 1.0, 0 < z < 0.1, x + 3y = 8 - z, and N contains at least one of F, Cl, and Br. The iron - based lithium - rich material with the above chemical formula can provide a large number of available active lithium ions for the secondary battery, thereby improving the cycle life of the secondary battery and reducing the internal resistance of the secondary battery.

[0031] In some embodiments, the average thickness of the outer shell is 2 - 25 nm. Exemplarily, the average thickness of the outer shell can be any value or the range between any two values among 2 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 18 nm, 20 nm, 22 nm, and 25 nm. When the average thickness of the outer shell is within the above range, it can improve the high - temperature storage performance of the secondary battery while maintaining a relatively high specific capacity of the lithium - supplementing material.

[0032] In some embodiments, the average thickness of the shell is 8-16 nm.

[0033] In some embodiments, the mass of the shell accounts for 0.2% to 3.0% of the total mass of the lithium supplement material. Exemplarily, the mass of the shell accounts for any one of 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0% of the total mass of the lithium supplement material or a range between any two values. When the mass proportion of the shell is within the above range, it is possible to improve the high temperature storage performance of the secondary battery while maintaining a high gram capacity of the lithium supplement material.

[0034] In some embodiments, the mass of the shell accounts for 0.8% to 2.5% of the total mass of the lithium supplement material.

[0035] In some embodiments, the particle strength of the lithium supplement material is greater than or equal to 80 MPa. Exemplarily, the particle strength of the lithium supplement material can be any one of 80 MPa, 90 MPa, 100 MPa, 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, 160 MPa, 170 MPa, 180 MPa, 190 MPa, 200 MPa, 210 MPa, and 220 MPa, or a range between any two values. When the particle strength of the lithium supplement material is within the above range, the particles are not easy to crack, which can further reduce gas production during high-temperature storage.

[0036] In some embodiments, the particle strength of the lithium supplementing material is greater than or equal to 100 MPa.

[0037] The second aspect of the present application provides a method for preparing a lithium supplement material, comprising the following steps:

[0038] S1. The lithium source and the iron source are mixed evenly and then sintered for the first time in an oxygen atmosphere to obtain a sintered product, wherein the first sintering temperature is 450 to 600 ° C and the first sintering time is 5 to 15 h;

[0039] S2. The N source and the primary sintered product are mixed and then sintered for a second time in an oxygen atmosphere to obtain a core material, wherein the second sintering temperature is 600 to 900 ° C, the second sintering time is 24 to 72h, and the N source comprises at least one of LiF, LiCl, and LiBr;

[0040] S3. After the lithium source, M source and core material are evenly mixed, they are sintered for a third time in an oxygen atmosphere to obtain a lithium supplement material, wherein the temperature of the third sintering is 700-1000° C. and the time of the third sintering is 6-12 hours.

[0041] In some embodiments, the lithium source includes at least one of LiOH, Li2O2, Li2O, and Li2CO3.

[0042] In some embodiments, the iron source includes at least one of FeOOH, FeO, and Fe2O3.

[0043] In some embodiments, the M source includes at least one of ruthenium dioxide, indium oxide, indium nitrate, gallium oxide, gallium nitrate, molybdenum oxide, and niobium oxide.

[0044] In a third aspect of the present application, a secondary battery is provided, wherein the secondary battery comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the lithium supplement material described in the present application. The positive electrode active material layer of the secondary battery described in the present application comprises the lithium supplement material described in the present application, thereby having excellent high temperature storage performance.

[0045] In some embodiments, the mass percentage of the lithium supplement material in the positive electrode active material is 0.5-5%. Exemplarily, the mass percentage of the lithium supplement material in the positive electrode active material can be any one of 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range between any two values.

[0046] In some embodiments, the secondary battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material.

[0047] The type of negative electrode active material is not specifically limited and can be selected according to actual needs. For example, the negative electrode active material can be artificial graphite, natural graphite, silicon-carbon composite material, silicon oxide, hard carbon, lithium metal and lithium titanate.

[0048] The type of negative electrode current collector is not particularly limited and can be selected according to actual needs. Preferably, copper foil or carbon-coated copper foil can be used.

[0049] In some embodiments, the secondary battery further comprises a separator. The type of separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, a polyethylene film, a polyvinylidene fluoride, a spandex film, an aramid film, or a multilayer composite film modified by a coating.

[0050] In some embodiments, the preparation of a secondary battery includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then winding them into a square bare cell, loading them into a battery casing, and then baking them at 65 to 95°C to remove water, injecting electrolyte, sealing, and obtaining a secondary battery after standing, hot and cold pressing, formation, clamping, capacity division and other processes.

[0051] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as one or more of polypropylene, polybutylene terephthalate, polybutylene succinate, etc.

[0052] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.

[0053] In the fourth aspect of the present application, an electric device is provided, and the electric device includes the secondary battery described in the third aspect of the present application. The electric device can be an application device such as a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. The vehicle can be a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, etc.; the spacecraft includes an airplane, a rocket, a space shuttle, and a spacecraft, etc.; the electric toy includes a fixed or mobile electric toy, for example, a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc.; the electric tool includes a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and a railway electric tool, for example, an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned devices.

[0054] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.

[0055] Example 1

[0056] Embodiment 1 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0057] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0058] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0059] S3. The precursor and 26 mg of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0060] S4. The above-obtained material, 44.4 mg of lithium carbonate and 159.6 mg of ruthenium dioxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained, which was then heated to 900°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined for 12 hours to obtain LiRuO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0061] Example 2

[0062] Embodiment 2 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0063] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0064] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0065] S3. The precursor and 26 mg of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0066] S4. The above-obtained material, 14.8 mg lithium carbonate and 53.2 mg ruthenium dioxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 900 ° C in an oxygen atmosphere at a heating rate of 5 ° C / min and calcined for 12 hours to obtain LiRuO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0067] Example 3

[0068] Embodiment 3 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0069] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0070] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0071] S3. The precursor and 26 mg of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0072] S4. The above-obtained material, 2.96 mg lithium carbonate and 10.6 mg ruthenium dioxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 900°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined for 12 hours to obtain LiRuO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0073] Example 4

[0074] Embodiment 4 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0075] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0076] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0077] S3. The precursor and 26 mg of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0078] S4. The above-obtained material, 14.8 mg lithium carbonate and 0.18 g gallium oxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained, which was then heated to 900 ° C in an oxygen atmosphere at a heating rate of 5 ° C / min and calcined for 12 hours to obtain LiGaO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0079] Example 5

[0080] Embodiment 5 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0081] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0082] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0083] S3. The precursor and 26 mg of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF0.05 O 3.95 Material.

[0084] S4. The above-obtained material, 14.8 mg lithium carbonate and 55.6 mg indium trioxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained, which was then heated to 900 ° C in an oxygen atmosphere at a heating rate of 5 ° C / min and calcined for 12 hours to obtain LiInO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0085] Example 6

[0086] Embodiment 6 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0087] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0088] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0089] S3. The precursor and 26 mg of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0090] S4. The above-obtained material, 14.8 mg of lithium carbonate and 53.2 mg of niobium pentoxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained, which was then heated to 900°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined for 12 hours to obtain LiNbO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0091] Example 7

[0092] Embodiment 7 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0093] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0094] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0095] S3. The precursor and 26 mg of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0096] S4. The above-obtained material, 14.8 mg lithium carbonate and 57.6 mg molybdenum trioxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained, which was then heated to 900 ° C in an oxygen atmosphere at a heating rate of 5 ° C / min and calcined for 12 hours to obtain LiMoO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0097] Example 8

[0098] Embodiment 8 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0099] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0100] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0101] S3. The precursor and 43 mg of lithium chloride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF0.05 O 3.95 Material.

[0102] S4. The above-obtained material, 14.8 mg lithium carbonate and 53.2 mg ruthenium dioxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 900 ° C in an oxygen atmosphere at a heating rate of 5 ° C / min and calcined for 12 hours to obtain LiRuO2-coated Li 4.95 FeCl 0.05 O 3.95 Material.

[0103] Example 9

[0104] Embodiment 9 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0105] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0106] S2. The raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0107] S3. The precursor and 87 mg of lithium bromide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0108] S4. The above-obtained material, 14.8 mg lithium carbonate and 53.2 mg ruthenium dioxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 900 ° C in an oxygen atmosphere at a heating rate of 5 ° C / min and calcined for 12 hours to obtain LiRuO2-coated Li 4.95 FeBr 0.05 O 3.95 Material.

[0109] Comparative Example 1

[0110] Comparative Example 1 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0111] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0112] S2. The mixed raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0113] S3. The ground precursor powder is heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min, calcined, kept at this temperature for 48 hours, and then cooled to room temperature in the furnace; after cooling, ground into powder to obtain Li5FeO4 lithium supplement material.

[0114] Comparative Example 2

[0115] Comparative Example 2 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0116] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0117] S2. The mixed raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0118] S3. The precursor and 0.1 g of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0119] Comparative Example 3

[0120] Comparative Example 3 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0121] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0122] S2. The mixed raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0123] S3. The ground precursor powder is heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min, calcined, kept at this temperature for 48 hours, and then cooled to room temperature in the furnace; after cooling, ground into powder to obtain Li5FeO4 lithium supplement material.

[0124] S4. Add the above-obtained material, 0.07g lithium carbonate and 0.26g ruthenium dioxide into a ball mill at a rotation speed of 400rpm. After 2 hours, a uniformly mixed mixture is obtained. Then, the mixture is heated to 900℃ in an oxygen atmosphere at a heating rate of 5℃ / min and calcined. The mixture is kept warm for 12 hours to obtain LiRuO2-coated Li5FeO4 material.

[0125] Comparative Example 4

[0126] Comparative Example 4 provides a lithium supplement material, and the specific preparation process of the lithium supplement material includes:

[0127] S1. Take 24.2g of lithium hydroxide and 14.4g of ferrous oxide and weigh them into a stirring tank, add 100mL of deionized water and stir and disperse at a speed of 600rpm per minute for 4 hours, and then vacuum dry to obtain a mixed raw material;

[0128] S2. The mixed raw material obtained above was heated to 500°C in an oxygen atmosphere at a heating rate of 2°C / min and calcined, kept warm for 10 hours, and then cooled to room temperature with the furnace; after cooling, ground into powder to obtain a precursor;

[0129] S3. The precursor and 0.1 g of lithium fluoride were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained. The mixture was then heated to 800°C in an oxygen atmosphere at a heating rate of 5°C / min and calcined. The mixture was kept at this temperature for 48 hours and then cooled to room temperature. After cooling, the mixture was ground into powder to obtain Li 4.95 FeF 0.05 O 3.95 Material.

[0130] S4. The above-obtained material, 14.8 mg lithium carbonate and 20.4 mg aluminum oxide were added to a ball mill at a speed of 400 rpm. After 2 hours, a uniform mixture was obtained, which was then heated to 900 ° C in an oxygen atmosphere at a heating rate of 5 ° C / min and calcined for 12 hours to obtain LiAlO2-coated Li 4.95 FeF 0.05 O 3.95 Material.

[0131] The physical properties of the lithium supplement materials in Examples 1 to 9 and Comparative Examples 1 to 4 are shown in Table 1.

[0132] Table 1

[0133]

[0134] The lithium supplement materials prepared in the examples and comparative examples were used as lithium supplement agents to prepare secondary batteries, and performance tests were performed. The specific methods are as follows:

[0135] (1) Battery assembly:

[0136] (1.1) Preparation of positive electrode sheet: The lithium supplement prepared in each embodiment and comparative example was dispersed in NMP with lithium iron phosphate, conductive agent acetylene black, dispersant PVP and binder polyvinylidene fluoride in a mass ratio of 2:95:0.8:0.4:1.8 to prepare a slurry, which was then coated on both sides of aluminum foil. After baking, rolling and cutting, a positive electrode sheet (surface density 0.22 g / 1540.25 mm 2 );

[0137] (1.2) Preparation of negative electrode sheet: Artificial graphite, conductive agent acetylene black, thickener CMC and binder SBR were mixed and dispersed in deionized water in a mass ratio of 96.4:0.8:1.5:1.3 to prepare a slurry, which was then coated on both sides of the copper foil. After baking, rolling and cutting, the negative electrode sheet (surface density 0.135 g / 1540.25 mm 2 );

[0138] (1.3) Preparation of electrolyte: EC and DMC were mixed in a volume ratio of 1:1, and then lithium hexafluorophosphate was added in a glove box to prepare an electrolyte with a concentration of 1 mol / L;

[0139] (1.4) The prepared positive electrode sheet, polyethylene separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets. The bare cell is obtained by winding, hot pressing, and welding the tabs. The bare cell is placed in an outer packaging aluminum-plastic film and baked in an oven at 85±10℃ for 24h. The electrolyte is injected into the dried battery and allowed to stand at high temperature to obtain a lithium-ion soft-pack battery.

[0140] (2) Testing of lithium-ion soft-pack batteries:

[0141] (2.1) Charging capacity test of lithium supplement: At 25±2°C, the secondary batteries obtained in each embodiment and comparative example were subjected to constant current charge and discharge test at a rate of 0.2C in the working range of 2.5-3.65V to obtain the initial charging capacity C i, the total mass of the lithium supplement + active material on the positive electrode is m0; the charging capacity of the active material is C0; the charging capacity of the lithium supplement is: C 补 =(C i -0.95m0C0) / 0.02m0.

[0142] (2.2) Internal resistance test: The soft-pack batteries obtained in the examples and comparative examples were formed and capacity-divided, and soft-pack batteries with similar performance were selected for high-temperature cycle test. After 1000 cycles, the soft-pack batteries were taken out and the SOC was adjusted to 50%. The batteries were discharged at a rate of 1C for 10s, and the voltage difference before and after discharge was recorded. The resistance value was obtained using Ohm's law.

[0143] (2.3) High-temperature storage gas generation test: First, the volume V0 of the soft-pack battery obtained in the embodiment and the comparative example was tested by the water displacement method, and then placed in a 70°C constant temperature box for 30 days. After taking out, the volume V1 of the soft-pack battery was recorded, and the volume expansion rate was calculated.

[0144] Table 2

[0145]

[0146] From the above embodiments and comparative examples, by doping specific non-metallic elements into iron-based lithium-rich materials and using specific layered lithium metal oxides as shell components, the high-temperature storage performance of the secondary battery is improved, the safety of the secondary battery is improved, the internal resistance of the secondary battery is reduced, and at the same time, the higher charging capacity of the iron-based lithium-rich material is maintained.

[0147] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A lithium supplement material, characterized in that: It comprises a core and an outer shell, wherein the core comprises an iron-based lithium-rich material, and the iron-based lithium-rich material contains a non-metallic element with an electronegativity greater than that of an oxygen element; The housing contains a layered lithium metal oxide with the chemical formula Li a MO 2+q , where 0.95 ≤ a ≤ 1.05, -0.05 < q < 0.05, and M contains at least one of Ru, Ga, In, Nb, and Mo.

2. The lithium supplement material according to claim 1, characterized in that: The non-metallic element includes at least one of fluorine, chlorine and bromine.

3. The lithium supplement material according to claim 1, characterized in that: The iron-based lithium-rich material contains a compound with the chemical formula Li x Fe y N z O 4-z , where 4.5 < x ≤ 5.0, 0.9 < y ≤ 1.0, 0 < z < 0.1, x + 3y = 8 - z, and N contains at least one of F, Cl, and Br.

4. The lithium supplement material according to claim 1, characterized in that: The average thickness of the shell is 2 to 25 nm.

5. The lithium supplement material according to claim 1, characterized in that: The mass of the shell accounts for 0.2% to 3.0% of the total mass of the lithium supplement material.

6. The lithium supplement material according to claim 1, characterized in that: The particle strength of the lithium supplement material is greater than or equal to 80 MPa.

7. The method for preparing the lithium supplement material according to any one of claims 1 to 6, characterized in that: The steps include: S1. The lithium source and the iron source are mixed evenly and then sintered for the first time in an oxygen atmosphere to obtain a sintered product, wherein the first sintering temperature is 450 to 600 ° C and the first sintering time is 5 to 15 h; S2. The N source and the primary sintered product are mixed and then sintered for a second time in an oxygen atmosphere to obtain a core material, wherein the second sintering temperature is 600 to 900 ° C, the second sintering time is 24 to 72h, and the N source comprises at least one of LiF, LiCl, and LiBr; S3. After the lithium source, M source and core material are evenly mixed, they are sintered for a third time in an oxygen atmosphere to obtain a lithium supplement material, wherein the temperature of the third sintering is 700-1000° C. and the time of the third sintering is 6-12 hours.

8. The method for preparing the lithium supplement material according to claim 7, characterized in that: The lithium source includes at least one of LiOH, Li2O2, Li2O, and Li2CO3; the iron source includes at least one of FeOOH, FeO, and Fe2O3; and the M source includes at least one of ruthenium dioxide, indium oxide, indium nitrate, gallium oxide, gallium nitrate, molybdenum oxide, and niobium oxide.

9. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer arranged on at least one side of the positive electrode collector, and the positive electrode active material layer comprises the lithium supplement material according to any one of claims 1 to 6 or the lithium supplement material prepared by the preparation method according to any one of claims 7 to 8.

10. An electrical device, characterized in that: The electric device comprises the secondary battery according to claim 9.